Loss of tumor suppressor WWOX accelerates pancreatic cancer development through promotion of TGFβ/BMP2 signaling - Hussam Husanie; Muhannad Abu-Remaileh; Kian Maroun; Lina Abu-Tair; Hazem Safadi; Karine Atlan; Talia Golan; Rami I. Aqeilan (Cell Death and Disease, 2022)
Abstract Pancreatic cancer is one of the most lethal cancers, owing to its late diagnosis and resistance to chemotherapy. The tumor suppressor WW domain-containing oxidoreductase (WWOX), one of the most active fragile sites in the human genome (FRA16D), is commonly altered in pancreatic cancer. However, the direct contribution of WWOX loss to pancreatic cancer development and progression remains largely unknown. Here, we report that combined conditional deletion of Wwox and activation of KRasG12D in Ptf1a-CreER-expressing mice results in accelerated formation of precursor lesions and pancreatic carcinoma. At the molecular level, we found that WWOX physically interacts with SMAD3 and BMP2, which are known activators of the TGF-β signaling pathway. In the absence of WWOX, TGFβ/BMPs signaling was enhanced, leading to increased macrophage infiltration and enhanced cancer stemness. Finally, overexpression of WWOX in patient-derived xenografts led to diminished aggressiveness both in vitro and in vivo. Overall, our findings reveal an essential role of WWOX in pancreatic cancer development and progression and underscore its role as a bona fide tumor suppressor.